Improving the Competence of Teacher Candidate: Evaluation of the Effectiveness of Experiential Learning GURU Model assisted by Flip-HTML : : Evaluation of the Effectiveness of Experiential Learning GURU Model assisted by Flip-HTML - Nirtha, Eva; Patawaran, Nilfred; Jecsen Pongkendek, Jesi; Loupatty, Martha (IJBLE Scientific Publications Community Inc., 2023)
This study aims to evaluate the effectiveness of the Experiential Learning GURU Model Flip-HTML assisted by Flip-HTML. This research uses the CIPP evaluation method by Stuffbleam, which consists of context, inputs, processes, and products. The research approach uses a mixed method approach, namely the sequential exploratory model, using a qualitative approach first, then the next stage using a quantitative approach. Data collection techniques use questionnaires, observation, and interviews. The subject of research is prospective primary school education teachers. Qualitative data were analyzed using the Miles and Huberman model, while quantitative data were processed by calculating percentages and categorization. The results of this study show that the context has been perfect, the input is quite good, the process is excellent, and the results are categorized as very good. Thus, the Experiential Learning model of Flip-HTML assisted teachers effectively improves prospective teachers' competence, but it still requires adequate internet facilities so that all prospective teachers can easily access it